2020
DOI: 10.1101/2020.08.06.237271
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

White Matter Disruption in Pediatric Traumatic Brain Injury: Results from ENIGMA Pediatric msTBI

Abstract: Annually, approximately 3 million children around the world experience traumatic brain injuries (TBIs), of which up to 20% are characterized as moderate to severe (msTBI) and/or have abnormal imaging findings. Affected children are vulnerable to long-term cognitive and behavioral dysfunction, as injury can disrupt or alter ongoing brain maturation. Post-injury outcomes are highly variable, and there is only limited understanding of how inter-individual differences in outcomes arise. Small sample sizes have als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…In line with prior publications, 31 we divided msTBI participants into three post-injury windows: (i) acute/sub-acute (MRI within 7 weeks of injury), during which pathology such as intracerebral hemorrhage and edema dominate; (ii) post-acute (MRI 8 weeks -6 months after injury), where secondary injuries such as regional atrophy and microstructural alterations become apparent; and chronic (MRI more than 6 months after injury), when some recovery and/or atrophy continues, but the brain is considered to be more stable. As discussed in a prior paper, 31 the exact boundaries were based on published data and natural break points within our datasets. Within the msTBI group, 67 scans were conducted during the acute phase, 122 during the post-acute, and 224 during the chronic phase of injury.…”
Section: Study Samplessupporting
confidence: 83%
See 2 more Smart Citations
“…In line with prior publications, 31 we divided msTBI participants into three post-injury windows: (i) acute/sub-acute (MRI within 7 weeks of injury), during which pathology such as intracerebral hemorrhage and edema dominate; (ii) post-acute (MRI 8 weeks -6 months after injury), where secondary injuries such as regional atrophy and microstructural alterations become apparent; and chronic (MRI more than 6 months after injury), when some recovery and/or atrophy continues, but the brain is considered to be more stable. As discussed in a prior paper, 31 the exact boundaries were based on published data and natural break points within our datasets. Within the msTBI group, 67 scans were conducted during the acute phase, 122 during the post-acute, and 224 during the chronic phase of injury.…”
Section: Study Samplessupporting
confidence: 83%
“…Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) is a global consortium of researchers aimed at achieving greater statistical power through harmonized processing of legacy data. Combining 12 cohorts shared within the ENIGMA Pediatric Moderate/Severe TBI (msTBI) working group, 31,32 we measured regional cerebellar volume in a cohort of 598 children/adolescents, including those with mild complicated-severe TBI (msTBI; n = 314) or without TBI (non-TBI; n = 284) and examined its associations with white matter microstructure and executive functioning. We hypothesized that (1) cerebellar volume would be lower in participants with msTBI than the non-TBI group, that (2) these disruptions would be most prominent in patients furthest from the time of injury, and that (3) smaller cerebellar volume would be associated with poorer executive functioning.…”
Section: (Which Was Not Certified By Peer Review) Preprintmentioning
confidence: 99%
See 1 more Smart Citation
“…[23][24][25] It was built on the framework created by the ENIGMA consortium, which seeks to achieve greater statistical power through harmonized image processing and meta/mega-analysis. 26 The ENIGMA Diffusion Tensor Imaging (DTI) workflow 27 has been used to identify altered WM organization across a range of disorders, including moderate/severe TBI in pediatric patients, 28 post-traumatic stress disorder (PTSD), 29 major depression, 30 and other conditions. 31 We used the ENIGMA DTI workflow to analyze asymmetry of WM organization in military brain injury across sixteen cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…There is limited research into the effects of early TBI on WM integrity several years post-injury; however, a large study of children and adolescents with moderate-to-severe TBI found disruptions to the integrity of various WM tracts at the acute/subacute, postacute, and chronic (6–26 months) post-injury periods ( 14 ). Specifically, significantly lower FA and higher MD was observed across tracts in those with TBI, relative to controls, at all three post-injury periods.…”
Section: Introductionmentioning
confidence: 99%